Effect of advanced platelet-rich fibrin applications on periodontal regeneration in infrabony pocket treatment - Christopher Imantaka Suwondo; Dahlia Herawati; Sudibyo Sudibyo (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
One of the regenerative periodontal treatments for infrabony pocket is open flap debridement (OFD) with the addition of growth factor derived from platelet concentrate. Advanced platelet-rich fibrin (A-PRF) is a further development of plateletrich fibrin (PRF) with a lower centrifugation speed (1,500 rpm, 14 minutes). The purpose of this study was to examine the differences in periodontal tissue regeneration after the application of A-PRF and PRF in the treatment of infrabony pockets evaluated from probing depth (PD), relative attachment loss (RAL), and alveolar bone height. The samples were taken from 20 infrabony pockets divided into 2 groups: 10 subjects were treated with OFD+A-PRF and OFD+PRF on the remaining subjects. Probing depth (PD) and relative attachment loss (RAL) measurement were performed on days 0, 30, and 90. Bone height measurements were performed using CBCT X-rays on days 0 and 90. The results showed that PD and RAL reduction in the group of OFD+A-PRF was significantly greater than that in the OFD+PRF group. Bone height reduction in both groups showed no difference. The conclusion obtained from this study is A-PRF application enhances periodontal tissue regeneration by generating greater probing depth and relative attachment loss reduction compared toPRF, as well as an increase in bone height similar to in the treatment of infrabony pockets.